Peningkatan Kemampuan Menulis Teks LHO dengan Pendekatan Genre-Based Approach (GBA) Siswa Kelas X - Ilma Amalia Alam; Abdul Azis; Yuli Astuti Amelia (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study aims to improve the ability to write Observation Report text of class X students of SMK Negeri 10 Makassar through various stages applied in the Genre-Based Approach (GBA). Data were obtained during planning, action implementation, observation and reflection through tests, classroom observation, and documentation. The test was conducted three times (initial test, cycle I test, and cycle II test). The research instruments used were LHO text writing skill test questions, analysis sheets, and observation sheets, as well as documentation guides. The research method used was classroom action research (PTK) which was carried out in two cycles. In cycle I, the results showed that only about 40% or 12 students managed to reach the Minimum Completion Criteria (KKM) and as many as 60% or 18 students who did not reach the KKM. However, after improvement and repetition through cycle II, the percentage of students who reached the KKM increased significantly to 90%. The results showed that the Genre-Based Approach (GBA) approach was able to improve the writing skills of the Observation Report text. This study concludes that the Genre-Based Approach (GBA) approach is effective in helping students master the writing of observation reports.